A detailed genetic map of the chromosome 7 bronchial hyper-responsiveness locus. - Leaves,NI; Bhattacharyya,S; Wiltshire,S; Cookson,WOCM (Eur J Hum Genet, 2002)
Non-specific bronchial hyper-responsiveness to various inhaled stimuli is a characteristic of asthma. We have previously shown linkage of bronchial responsiveness to methacholine (measured as dose-response slope (DRS)) and the peripheral blood eosinophil count (EOS) to chromosome 7. We have now further investigated these linkages by genotyping 49 microsatellite markers across the DRS locus on chromosome 7. The markers were spaced on average 2.6 cM apart and spanned a sex averaged cumulative genetic distance of 129 cM. Multipoint linkage to DRS was bimodal and dipped at the centromere. The two peaks of linkage were close to markers D7S484 (P=0.0003) and D7S669 (P=0.006) respectively. Separate testing for linkage to paternally and maternally derived alleles showed that the linkage near D7S484 was paternally derived (P<0.00001): maternally derived alleles did not exhibit significant linkage. The results indicate that two disparate loci may be influencing asthma from chromosome 7.